Characteristics of Refill Drinking Water Depot and Bacteriology Evaluation in Covid-19 Period - Herniwanti, Herniwanti; Endang Purnawati Rahayu; Yen Purwawinata Mohan (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Accessing the characteristics of Refill Drinking Water Depot (DAMIU) is the initial step in mapping the quality of water to be processed into drinking water. Therefore, this study aims to map the characteristics and bacteriology of DAMIU raw water at the Koto Kampar Hulu sub-district to prevent COVID-19. This was a study conducted using a qualitative approach with 7 raw water samples. The bacteriology of Raw Water (E. Coli and Coliform) is an indicator of the required standards in line with the minister of health regulation No.32 of 2017. Furthermore, the results showed that 85% of the DAMIU raw water originated from drilling and dug wells. The distance to water sources was mostly <20 km. Bacteriological tests for E. Coli were consistent with the quality standards while 4 DAMIU sources contain Coliform bacteria due to poor hygiene. Hence, it is recommended that the health department, responsible for consumer protection and law enforcement, provide guidance and supervision to DAMIU entrepreneurs that failed to meet the requirements. Further PAMSIMAS, PHBS, and STMB programs as well as other technological innovations are needed to provide a drinking water source that is healthy, cheap, and protected from disease during the COVID-19 period.